Identification of a subunit of NADH-dehydrogenase as a p49/STRAP-binding protein - Zhong Ying; Helms Scott; Azhar Gohar; Zhang Xiaomin; Wei Jeanne Y (BMC Cell Biology, 2008)
Abstract Background The p49/STRAP (or SRFBP1) protein was recently identified in our laboratory as a cofactor of serum response factor that contributes to the regulation of SRF target genes in the heart. Results In the present study, we report that NDUFAB1, a nuclear encoded subunit of NADH dehydrogenase, represented the majority of the cDNA clones that interacted with p49/STRAP in multiple screenings using the yeast two-hybrid system. The p49/STRAP and NDUFAB1 proteins interacted and co-localized with each other in the cell. The p49/STRAP protein contains four classic nuclear localization sequence motifs, and it was observed to be present predominantly in the nucleus. Overexpression of p49/STRAP altered the intracellular level of NAD, and reduced the NAD/NADH ratio. Overexpression of p49/STRAP also induced the deacetylation of serum response factor. Conclusion These data suggest that p49/STRAP plays a role in the regulation of intracellular processes such as cardiac cellular metabolism, gene expression, and possibly aging.